Oxocarbon Salts for Fast Rechargeable Batteries. (8th September 2016) - Zhao, Qing; Wang, Jianbin; Lu, Yong; Li, Yixin; Liang, Guangxin; Chen, Jun
Abstract: Oxocarbon salts (M2 (CO) n ) prepared through one‐pot proton exchange reactions with different metal ions (M=Li, Na, K) and frameworks ( n =4, 5, 6) have been rationally designed and used as electrodes in rechargeable Li, Na, and K‐ion batteries. The results show that M2 (CO)5 /M2 (CO)6 salts can insert two or four metal ions reversibly, while M2 (CO)4 shows less electrochemical activity. Especially, we discover that the K2 C6 O6 electrode enables ultrafast potassium‐ion insertion/extraction with 212 mA h g −1 at 0.2 C and 164 mA h g −1 at 10 C. This behavior can be ascribed to the natural semiconductor property of K2 C6 O6 with a narrow band gap close to 0.9 eV, the high ionic conductivity of the K‐ion electrolyte, and the facilitated K‐ion diffusion process. Moreover, a first example of a K‐ion battery with a rocking‐chair reaction mechanism of K2 C6 O6 as cathode and K4 C6 O6 as anode is introduced, displaying an operation voltage of 1.1 V and an energy density of 35 Wh kg −1 . This work provides an interesting strategy for constructing rapid K‐ion batteries with renewable and abundant potassium materials.